2022
DOI: 10.1186/s13045-022-01359-4
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblast-specific lncRNA LINC01614 enhances glutamine uptake in lung adenocarcinoma

Abstract: Background Besides featured glucose consumption, recent studies reveal that cancer cells might prefer “addicting” specific energy substrates from the tumor microenvironment (TME); however, the underlying mechanisms remain unclear. Methods Fibroblast-specific long noncoding RNAs were screened using RNA-seq data of our NJLCC cohort, TCGA, and CCLE datasets. The expression and package of LINC01614 into exosomes were identified using flow cytometric so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 54 publications
(69 reference statements)
0
48
0
Order By: Relevance
“…CAFs play a significant role in tumor progression by secreting various factors, such as growth factors, extracellular matrix proteins, and immunosuppressive ligands, which also contribute to the immunosuppressive effects of the TME ( 40 ). In LUAD, CAFs promote cancer progression by enhancing glutamine uptake in LUAD cells through CAF-specific long-chain non-coding RNA LINC01614 packaged in secreted exosomes ( 41 ). Furthermore, the reduction of extracellular CLCN3 secretion via HNRNPK knockdown inhibits CAF activation and TGF-β1 production.…”
Section: Discussionmentioning
confidence: 99%
“…CAFs play a significant role in tumor progression by secreting various factors, such as growth factors, extracellular matrix proteins, and immunosuppressive ligands, which also contribute to the immunosuppressive effects of the TME ( 40 ). In LUAD, CAFs promote cancer progression by enhancing glutamine uptake in LUAD cells through CAF-specific long-chain non-coding RNA LINC01614 packaged in secreted exosomes ( 41 ). Furthermore, the reduction of extracellular CLCN3 secretion via HNRNPK knockdown inhibits CAF activation and TGF-β1 production.…”
Section: Discussionmentioning
confidence: 99%
“…Glycolysis↑ OXPHOS↓ ECM acidification↑ [257] Tumor cell GC Lipid-ROS↓ Ferroptosis ↓ [258] Tumor cell BC Glycolysis↑ OXPHOS↓ Proliferation↑ [259] Tumor cell HCC Glycolysis↑ Migration, invasion↑ [260] Tumor cell LUAD Glutamine uptake↑ Tumorigenesis↑ [261] Tumor cell BC Glycolysis↑ HTR↑ [262] Tumor cell BC Glycolysis↑ OXPHOS↓ Tumorigenesis↑ [263] Tumor cell Laryngeal cancer Glycolysis↑ Proliferation↑ [264] Tumor cell BC Glycolysis↑ Apoptosis↓ [265] Tumor cell Melanoma FAO↑ Migration↑ [266] Tumor cell HCC GLUT-1↑ 5-FU resistance↑ [267] Tumor cell NPC Lipid accumulation↑ Proliferation, migration↑ [268] tryptophan 2, 3-dioxygenase (TDO) expression, resulting in enhanced secretion of Kyn, which ultimately activate AKT and STAT3 signaling pathways and induce chemoresistance [237]. (Table 3).…”
Section: Human Adult Dermal Fibroblastsmentioning
confidence: 99%
“…CAFs can regulate amino acid metabolism in lung adenocarcinoma (LUAD) cells via exosomes. CAFs-derived exosomal LINC01614 can interact with ANXA2, p65 and activate NF-κB pathway to promote the expression SLC38A2 and SLC7A5, thus enhancing tumor cells glutamine uptake [261]. Furthermore, CAFs-derived exosomal mtDNA may regulate hormonal therapy-resistant (HTR) in breast cancer patients.…”
Section: Cafs-derived Exosomal Cargos Induce Metabolic Reprogrammingmentioning
confidence: 99%
“…LncRNAs also participate in activation of LNFs to CAFs, whereas activated CAFs can change gene expression and secretion characteristics of NSCLC cells through lncRNAs [73]. Liu et al screened fibroblast-specific lncRNAs using RAN-seq data and identified LINC01614 promoting the secretion of IL-6 from cancer cells that upregulates LINC01614 in CAFs, constituting a feedforward loop between CAFs and NSCLC cells [74].…”
Section: Role Of Extracellular Vesicles In Communication Between Cafs...mentioning
confidence: 99%